Regional features of ionospheric disturbances during the intense geospace storm of November 4-5, 2023 - Chernogor, L. F.; Tkachenko, M. Yu. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 2024)
Relevance. The ionosphere is the main channel that ensures the functioning of radio communication, radionavigation, radar, remote radio sensing, and radio astronomy systems. The parameters of this channel significantly affect the quality and functionality of both terrestrial and space technological systems. The channel parameters are shaped by various factors within the Earth–atmosphere–ionosphere–magnetosphere (EAIM) system. The most influential factor is solar storms, which are accompanied by solar flares, solar cosmic radiation, and coronal mass ejections. These events greatly disturb the atmosphere–ionosphere–magnetosphere radio channels, leading to disruptions in the operation of radio systems for various purposes. Therefore, comprehensive research into radio channel disturbances is a relevant task.The aim of this work is to describe the results of research on the regional peculiarities of ionospheric disturbances through the analysis of derivatives from global ionospheric maps, specifically maps of percentage increases in total electron content (TEC) values.Methods and Methodology. The primary data used for this study are global ionospheric maps compiled by the Center for Orbit Determination in Europe, which are freely available on the website of The Crustal Dynamic Data Information System.Results. For the first time, using GNSS technologies, maps of percentage increases in TEC values in the ionosphere were constructed and studied, which can be interpreted as an ionospheric disturbance index. The response of TEC to the powerful geospace storm of November 4-5, 2023, was investigated. It was found that during most of the main phase of the magnetic storm, the largest ionospheric disturbances were observed at latitudes significantly lower than the Arctic and Antarctic Circles, indicating a reconfiguration of the ionosphere–magnetosphere current system, the emergence of significant currents, and a change in ionospheric weather conditions.